Radiographic Analysis of Total Ankle Replacements: A COFAS Study. Issue 3 (14th September 2018) - Le, Vu (Brian); Escudero, Mario; Penner, Murray; Wing, Kevin; Younger, Alastair; Veljkovic, Andrea; Barahona, Maximiliano
Category: Ankle Arthritis Introduction/Purpose: Total ankle replacements (TAR) are an increasingly common treatment for end-stage ankle arthritis but evidence on optimal alignment is not as well-established as in the hip and knee arthroplasty literature. Many believe that restoration of coronal and sagittal alignment is critical, while others suggest malalignment within a certain range has no impact on failure (Braito et al. 2015). There is controversy on the ideal TAR component positioning to minimize failure and requiring revision surgery. In this study we examine 9 radiographic measures of TARs, 6 of which have previously been described for TARs, 1 commonly used on preoperative ankles, and 2 novel measures on a database of 146 TARs to identify predictors of TAR re-operation. Methods: A retrospective review was performed on the Canadian Orthopaedic Foot and Ankle Society (COFAS) database of ankle arthritis, selecting for all total ankle replacements done at a single institution by one of three fellowship-trained foot and ankle surgeons between September 2004 and June 2015. Those with complete series of anteroposterior and lateral standing ankle radiographs both preoperative and postoperative, and minimum of 1 year of follow-up were included. Measurements were performed on the postoperative radiographs and included: coronal and sagittal distal tibial component angles, talar center migration, talar tilt angle, lateral talar station, tibial axis-talus ratio, talar component gamma angle, anterior and posterior tibial component overhang and underhang. Standard descriptive statistical methods were used to analyze the data. Results: Of a total of 296 TARs, 146 were included and 14 TARs failed (9.6%), defined as requiring re-operation, 8 of which were metal-component revisions (5%). The TARs were stratified into those with measurements within previously published normal values and those that fall outside that range. Time to failure ranged from 1.4 to 9.6 years. Our preliminary data analysis showed that TARs with coronal distal tibial component angles between 87-93 degrees demonstrated an odds ratio of 0.11 for re-operation compared with those beyond that range, p=0.003. TARs with talar tilt angles of 0 degrees demonstrated an odds ratio of 0.24 for re-operation compared with those whose talar tilt was not zero, p=0.02. Conclusion: Post-operative coronal alignment of TARs, namely distal tibial component angle and talar tilt, appear to be associated with TAR-reoperation. Specifically, if the measurements are within previously described normal limits, the odds ratio for re-operation is low and statistically significant. Further data analysis is underway and may demonstrate more parameters of significance in predicting TAR failure.